Degradome sequencing reveals an endogenous microRNA target in C. elegans. Issue 7 (26th February 2013) - Park, June Hyun; Ahn, Soungyub; Kim, Soyoung; Lee, Junho; Nam, Jin-Wu; Shin, Chanseok
Abstract : Caenorhabditis elegans microRNAs (miRNAs) bind to partially complementary sequences in the 3′ untranslated region of target mRNAs, resulting in translational repression through mRNA destabilization. High‐throughput sequencing of RNA cleavage fragments was performed to directly detect miRNA‐directed cleavage targets in adult stage C. elegans . From this analysis, we found that miR‐249 directed the cleavage of the ZK637.6 transcript with extensive and evolutionarily conserved complementarity in nematode. In addition, expression of the ZK637.6 transcript was strongly dependent on the expression of miR‐249. These findings may lead to a better understanding of miRNA‐mediated gene regulation in nematodes. Abstract : ► Degradome sequencing was employed to directly detect endogenous miRNA cleavage targets in C. elegans . ► miR‐249 directs the cleavage of the ZK637.6 pseudogene transcript. ► The expression of the ZK637.6 pseudogene transcript is negatively correlated with the expression of miR‐249.